Patulin-producing mold, toxicological, biosynthesis, and molecular detection of patulin - Ratih Paramastuti; Winiati Pudji Rahayu; Siti Nurjanah (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2021)
Mycotoxin is one of the food safety problems that raise concern because of its negative health impact and significant economic losses. Patulin is the most common mycotoxin found in fruits and its products like apple, orange, grape, pear, etc. There are 167 species reported to produce patulin; Penicillium expansum is the major patulin producer among those fungi species. Patulin is not classifiable as to its carcinogenicity to humans, but some studies showed the toxicities of patulin. Patulin has a broad spectrum of toxicity such as acute toxicity, sub-acute toxicity, genotoxicity, embryotoxicity and teratogenicity, carcinogenicity, and immunotoxicity. There are several ways to detect mycotoxins, such as HPLC, TLC, ELISA, and PCR. The popular way to detect mycotoxin molecularly is PCR because of its sensitivity and specificity. To detect patulin molecularly require proper selection of target gene. Therefore, the biosynthesis of patulin, its influencing gene, and its underlying factor needs to be understood.